Fabrication of large-area multi-scale-architectured thin-film SOFC via commercially viable thin-film technology - Noh, H.-S.; Hong, J.; Kim, H.; Yoon, K.J.; Kim, B.-K.; Lee, J.-H.; Son, J.-W. (Electrochemical Society Inc., 2015)
The feasibility of realizing large-area multi-scale-architectured thin-film solid oxide fuel cell (TF-SOFC) by using commercially viable thin-film technology, sputtering in the present study, is investigated. By using a 2-inch sputtering system, the multi-scale-architectured platform consisting of a nanostructure NiO-yttria-stabilized zirconia (YSZ) interlayer and an ultra-thin YSZ electrolyte is successfully fabricated over a 5 cm by 5 cm NiO-YSZ anode support. An open circuit voltage of 1.1 V and a peak power density exceeding 1 Wcm-2 are obtained; thus the total power output from the cell reaches 16 W at 600°C. The present study demonstrates the possibility of transferring the multi-scale-architectured TF-SOFC technology to the industrial sector using commercial thin-film technologies. ？ The Electrochemical Society.